Geography, niches, and transportation influence bovine respiratory microbiome and health - Chai, Jianmin; Liu, Xinting; Usdrowski, Hunter; Deng, Feilong; Li, Ying; Zhao, Jiangchao (Frontiers in Cellular and Infection Microbiology, 2022)
Bovine respiratory disease (BRD), one of the most common and infectious diseases in the beef industry, is associated with the respiratory microbiome and stressors of transportation. The impacts of the bovine respiratory microbiota on health and disease across different geographic locations and sampling niches are poorly understood, resulting in difficult identification of BRD causes. In this study, we explored the effects of geography and niches on the bovine respiratory microbiome and its function by re-analyzing published metagenomic datasets, and estimated the main opportunistic pathogens that changed after transportation. Results showed that diversity, composition, structure, and function of the bovine nasopharyngeal microbiota were different across three worldwide geographic locations. Lung microbiota also showed distinct microbial composition and function compared to nasopharyngeal communities from different locations. Although different signature microbiota for each geographic location were identified, a module with co-occurrence of Mycoplasma species was observed in all bovine respiratory communities regardless of geography. Moreover, transportation, especially long-distance shipping, could increase the relative abundance of BRD-associated pathogens. Lung microbiota from BRD calves shaped clusters dominated with different pathogens. In summary, geography, sampling niches and transportation are important factors impacting the bovine respiratory microbiome and disease, and clusters of lung microbiota by different bacterial species may explain BRD pathogenesis, suggesting the importance of a deeper understanding of bovine respiratory microbiota.